Evaluasi Dampak Pengaruh Program Keluarga Harapan Terhadap Pengeluaran Biaya Pendidikan di Indonesia - Wijaya, Heru Kusuma; Khoirudin, Rifki (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education is a valuable asset in the foundation of quality human resources in managing natural resources. It is a fact that Indonesia is ranked 65th out of 73 countries. Various countries have implemented Conditional Cash Transfer as an effort to overcome education quality problems, while in Indonesia the CCT program is called PKH. The main target of this program is to improve the quality of health and education. The aim of this research is to determine the impact of implementing the pkh program on education expenditures in Indonesia for children in the household, children outside the household and overall, using the IFLS Wave 5 data source. This research uses the Propensity Score Matching data processing method. The results of the research showed that the group that received the program was shown to significantly increase education expenditures for children in the household by 4.11, while for children outside the household it significantly decreased by 1.44, but the overall results increased by 3.58 per year. These results were almost the same as the 4 value test methods.